Effect of Current Ratio and Activity Ratio on Profitability in Food and Beverage Companies Listed on the Indonesia Stock Exchange (2018-2021) - Niarita Bukit; Sarmauli Hanny Siagian; Susan Grace V Nainggolan (Jurnal Ekonomi, 2023)
Today's people are increasingly liking and enjoying packaged food and drinks, in addition to the delicious and delicious taste, plus it is practical when taken anywhere. This is what triggers the growth and development of this industry. Thus it is necessary to measure the level of performance and to measure the performance of these companies is to use the SPSS 20 tool which uses company data that provides food and beverages listed on the Indonesia Stock Exchange to producetests run on the data show that Profitability is not significantly affected. This means that there is no correlation between variables.Liquidity variable (X1) of 0.789 is less than t table 2.026 or the significance value of the Liquidity variable 0.435 is more than 0.05. Likewise with the activity ratioThe activity variable has a t value of -0.331 which is smaller than the t table of 2.026 or the sig.t value of the activity variable is 0.743. This means that activity has no significant effect on profitability. Likewise simultaneously with a significance level of 0.731. F count <F table is 0.316 <3.24 when compared with F table at the 5% confidence level. Fcount <F table, it can be concluded that it has no effect